'Made to run': Biopolitical marketing and the making of the self-quantified runner. (September 2019) - Charitsis, Vassilis; Yngfalk, Anna Fyrberg; Skålén, Per
While previous critical marketing research on co-creation has focused on how consumers' cognitive and social abilities are governed, this article focuses on how firms' marketing strategies attempt to govern every aspect of consumers' lives. By drawing on a biopolitical framework and a study of Nike+, a marketing system for runners which Nike has developed around its self-tracking devices, three biopolitical marketing dimensions were identified: the gamification of the running experience, the transformation of running into a competitive activity and the conversion of running into a social activity. In identifying these marketing dimensions, the study demonstrates how self-tracking affordances are deployed in the development of a biopolitical marketing environment that tames, captures and appropriates value from different aspects of consumers' lives, including – and combining – their social behaviours, cognitive capacities and bodily conducts. This article contributes to critical studies of value co-creation by focusing on the tamed self-tracking body as a resource for value creation, but also by demonstrating that consumers engage, through cognitive labour, in the production of the biopolitical environment that leads to their exploitation.